The Association for Human Pharmacology in the Pharmaceutical Industry London Meeting October 2019: Impending Change, Innovation, and Future Challenges - Khan, Shahzadgai; Albayaty, Muna; Bush, James; Cheriyan, Joseph; Cromie, Anthea; Koch, Annelize; Hammond, Michael; Mair, Stuart; Lorch, Ulrike; Stringer, Steffan; Taubel, Jorg; Hardman, Timothy C. (Frontiers in Pharmacology, 2020)
The Association for Human Pharmacology in the Pharmaceutical Industry (AHPPI) annual meeting focused on impending change, innovation and future challenges facing early phase drug development as we move into the second decade of the twenty first century. The meeting opened with discussion around the technical revolution in pharmaceutical medicine over the four decades since the AHPPI was founded and how transformative technologies have accompanied the introduction of processes such as physiologically based pharmacokinetic modelling (PBPK). During the meeting examples were presented of how in terms of the development of new therapies, the classic phases of clinical drug development are becoming a thing of the past and the lines between the phases have begun to blur, particularly in the field of oncology The contribution that monoclonal antibodies have made to medicine and the next chapter in their design and use was also discussed. A representative of the UK's Medicine and Healthcare Products Regulatory Agency discussed the increasing numbers of requests to approve complex innovative design trials, how novel trial designs are impacting on the traditional linear 'phase' approach to drug development and the common pitfalls associated with them. Guidance was provided from a regulator's viewpoint on what was meant by the term 'novel design' and how to submit successful trial applications for such complex trials. In an Oxford-style debate, the audience discussed the motion that 'there is no longer a need to include placebo subjects in early clinical trials.' The keynote speaker focused on delivering change in complex environments such as the field of drug development. The afternoon session included presentations on the challenges associated with drug product design, the complexities within non-oral dosage forms and proposed new methods of formulations for drug delivery. Presentations were also given on advances in mechanistic and computational pharmacokinetic modelling and how they have proved to be valuable tools to rationalise and facilitate the process of drug development.